Financial and managerial accounting - Warrren, Carl; Reeve, James ;Duchac, Jonathan (South - Western : Cengage Learning Asia Pte Ltd, 2014)
Activate Learning with Warren/Reeve/Duchac's, FINANCIAL AND MANAGERIAL ACCOUNTING! Market-leading FINANCIAL AND MANAGERIAL ACCOUNTING has been on the forefront of innovation and change based on the needs of today's students. Warren offers you clear guidance to complete homework with an efficient presentation for today's learner. The high impact writing style and streamlined design makes important information accessible, with a focus on providing the best and most complete examples.
Keywords: MANAGERIAL ACCOUNTING